Development and Evaluation of the Qur'an Jar-Based HIDA Model as a Preventive Psychospiritual Intervention for Academic Burnout among Vocational High School Students - Astutik, Widiya; Musthofa, Indhra; Hakim, Dian Mohammad (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Academic burnout has become an increasingly important concern in vocational education due to the intensive academic workload, practical training demands, and workplace-oriented learning environment experienced by students. Despite growing attention to psychospiritual approaches for promoting student well-being, few studies have developed and empirically evaluated instructional interventions that systematically integrate Islamic values with educational technology. This study aimed to develop and evaluate the Qur'an Jar-Based HIDA Model as a preventive psychospiritual intervention for reducing academic burnout among vocational high school students. The study employed a Research and Development design using the ADDIE instructional design framework. The developed model was validated by experts in Islamic psychospiritual education, instructional design, and vocational education before being implemented with 33 twelfth-grade vocational students. Quantitative data were analyzed using Aiken's V and paired-samples t-tests, while qualitative data from QR code-based digital self-monitoring and students' reflective journals were analyzed thematically. The validation results indicated satisfactory content validity, confirming the conceptual appropriateness and instructional feasibility of the model. Following implementation, students demonstrated significant reductions in academic burnout and improvements in emotional balance. Qualitative findings further revealed increased emotional awareness, deeper spiritual reflection, and stronger commitments to positive behavioural change throughout the intervention. These findings suggest that integrating psychospiritual guidance, reflective learning, and technology-assisted self-monitoring provides an effective instructional approach for supporting students' psychological well-being. The Qur'an Jar-Based HIDA Model contributes to educational technology by offering an evidence-based framework that integrates instructional design, Islamic psychospiritual values, and digital monitoring to foster holistic student development in vocational education.